Odd-numbered very-long-chain fatty acids from the microbial, animal and plant kingdoms - Rezanka, Tomás; Sigler, Karel (Progress in lipid research, 2009)
Very long chain fatty acids (FAs) are important components of different classes of lipids in all organisms from bacteria to man. They include also, usually as minor components, odd-numbered FAs. These have so far been given little attention because of technical difficulties inherent in their detection and identification. Current modern analytical methods such as GC-MS and/or LC-MS make this detection and identification possible, and should promote a study of their properties. This review brings, in a concise manner, most of the currently available information about these FAs, their occurrence in different organisms, their structure and other properties. It should provide an impetus for further research into these very interesting compounds whose chemical, biochemical and biological properties are poorly known.
Keywords: houby; rostliny; Fatty Acids; mastné kyseliny; Yeasts; Plants; Decanoic Acids; zvířata; Humans; kyseliny dekanové; kvasinky; Fungi; Bacteria; Gas Chromatography-Mass Spectrometry; plynová chromatografie s hmotnostně spektrometrickou detekcí; lidé; Animals